Role of hospitals in recovery from COVID-19: Reflections from hospital managers and frontliners in the Eastern Mediterranean Region on strengthening hospital resilience - Ravaghi, Hamid; Khalil, Merette; Al-Badri, Jehan; Naidoo, Antoinette Vanessa; Ardalan, Ali; Khankeh, Hamidreza (Frontiers in Public Health, 2023)
Background COVID-19 highlighted the critical role that hospitals play throughout the prolonged response and continuous recovery stages of the pandemic. Yet, there is limited evidence related to hospitals in the recovery stage, particularly capturing the perspectives of hospital managers and frontliners in resource-restrained and humanitarian settings. Objective This paper aims to capture the perspectives of hospital managers and frontliners across the Eastern Mediterranean Region on (1) the role of hospitals in recovering from COVID-19, (2) Hospitals' expectations from public health institutions to enable recovery from COVID-19, (3) the Evaluation of hospital resilience before and through COVID-19, and (4) lessons to strengthen hospital resilience throughout the COVID-19 recovery. Methods A multi-methods approach, triangulating a scoping review with qualitative findings from 64 semi-structured key-informant interviews and survey responses (n = 252), was used to gain a deeper context-specific understanding. Purposeful sampling with maximum diversity supported by snowballing was used and continued until reaching data saturation. Thematic analysis was conducted using MAXQDA and simple descriptive analysis using Microsoft Excel. Findings In recovering from COVID-19, hospital managers noted hospitals' role in health education, risk reduction, and services continuity and expected human resource management, financial and material resource mobilization, better leadership and coordination, and technical support through the provision of updated clinical evidence-based information from their public health institutions. Qualitative findings also indicated that hospital managers attributed considerable changes in hospitals' resilience capacities to the pandemic and suggested that strengthening hospitals' resilience required resilient staff, sustainable finance, and adaptive leadership and management. Conclusion Hospitals are the backbone of health systems and a main point of contact for communities during emergencies; strengthening their resilience throughout the various stages of recovery is critical. Hospitals cannot be resilient in silos but rather require an integrated-whole-of-society-approach, inclusive of communities and other health systems actors.